Prolonged Fever Caused by Subacute Thyroiditis. A Case Report - Lisbet María Cortez Mijares; Ariel Martínez Lastre; Claribel Plain Pozos (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Female patient aged 44. A month before attending Medicine Emergency Services at the9 de Abril General Teaching Hospital she started having mild pain at the lateral neck with signs of inflammation, joint pain, malaise and weight loss. She also presented a fever of 38.5 ° C during 15 days of evolution, appearing mainly in the afternoons. No records of prior respiratory infectious process were collected. She was hospitalized and blood culture was performed. It resulted positive for Klebsiella pneumoniae and was treated with antibiotics and anti-inflammatories, thus achieving clinical improvement. The patient was released with a diagnosis of persistent fever and Quervain thyroiditis. After 15 days, the patient was asymptomatic.